Pengembangan Lembar Kerja Siswa Berbasis Inkuiri Terbimbing Untuk Meningkatkan Hasil Belajar Siswa Kelas XI SMA pada Materi Termokimia - Putu Ayu Momi Prameswari; Rahmanpiu; Maysara (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2023)
The research "Development of Guided Inquiry-Based Student Worksheets to Improve Learning Outcomes of Class XI High School Students on Thermochemistry Material" aims to test the quality of guided inquiry-based worksheets on thermochemistry material, test the practicality of guided inquiry-based worksheets on thermochemistry material, and test the effectiveness of using inquiry-based worksheets guided on thermochemistry material. This research method uses the 4-D Thiagarajan model, with research instruments in the form of expert validation sheets, multiple choice questions, and student response questionnaire sheets. The results showed that the guided inquiry-based worksheet products that had been developed were in the very valid category with an average percentage of 92.15%; with a decent category; and students' responses to LKPD reached a percentage of 90% in the proper category and the level of effectiveness reached 80% in the effective category.